Risk stratification scheme based on the TNM staging system for dogs with oral malignant melanoma centered on clinicopathologic presentation - Song, Eric; Lawrence, Jessica; Greene, Erica; Christie, Anneka; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2024)
IntroductionOral malignant melanoma (OMM) is the most common malignant oral neoplasm in dogs. Tumor recurrence, progression, and regional and distant metastasis remain major obstacles despite advanced therapy. Tumor size has been a consistent, key independent prognostic factor; however, other clinical and histopathologic features impact prognosis and likely influence optimal treatment strategies. Adoption of a risk stratification scheme for canine OMM that stratifies groups of dogs on defined clinicopathologic features may improve reproducible and comparable studies by improving homogeneity within groups of dogs. Moreover, it would aid in the generation of multidisciplinary prospective studies that seek to define optimal treatment paradigms based on defined clinicopathologic features.MethodsTo build a platform upon which to develop a risk stratification scheme, we performed a systematic review of clinicopathologic features of OMM, with particular attention to levels of evidence of published research and the quantitative prognostic effect of clinicopathologic features.ResultsTumor size and presence of bone lysis were repeatable features with the highest level of evidence for prognostic effects on survival. Overall, with strict inclusion criteria for paper review, the levels of evidence in support of other, previously proposed risk factors were low. Factors contributing to the challenge of defining clear prognostic features including inconsistencies in staging and reporting of prognostic variables, incomplete clinical outcome data, inhomogeneous treatment, and absence of randomized controlled studies.DiscussionTo overcome this in the future, we propose a risk stratification scheme that expands the TNM system to incorporate specific designations that highlight possible prognostic variables. The ability to capture key data simply from an expanded TNM description will aid in future efforts to form strong conclusions regarding prognostic variables and their influence (or lack thereof) on therapeutic decision-making and outcomes.